1995
DOI: 10.1007/bf02599947
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to screening mammography recommendations in a university general medicine clinic

Abstract: Acceptance of screening mammography recommendations decreases with age. Among the women who agreed to the recommendation for screening mammography, insurance type and health care provider level of training best predicted adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…6 While the gap in screening mammography use by race has narrowed, 7 mammography remains underused among minorities and women with less education, 3,8,9 even those receiving physician recommendations for mammography. 10 A 1998 Annals of Internal Medicine editorial reported that "to harness the full benefit of early detection, we must understand and overcome barriers to mammography use in ethnic minority populations." 11 To address this need, we developed and evaluated a community-based breast cancer education program for older women and implemented the program through an urban social service organization.…”
mentioning
confidence: 99%
“…6 While the gap in screening mammography use by race has narrowed, 7 mammography remains underused among minorities and women with less education, 3,8,9 even those receiving physician recommendations for mammography. 10 A 1998 Annals of Internal Medicine editorial reported that "to harness the full benefit of early detection, we must understand and overcome barriers to mammography use in ethnic minority populations." 11 To address this need, we developed and evaluated a community-based breast cancer education program for older women and implemented the program through an urban social service organization.…”
mentioning
confidence: 99%
“…Women's lack of resources, combined with cultural or attitudinal barriers and limited access to affordable mammography, may directly reduce the likelihood of use, both in the absence of a physician recommendation and following one. 44,45 Interventions to increase appropriate physician recommendation must be accompanied by complementary efforts that help women overcome economic barriers to mammography use. Interventions must also be accompanied by outreach efforts that prompt women to obtain mammography, encourage women to talk with their physicians about referral for mammography, and assist women in overcoming barriers to compliance with physician recommendation for mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Dolan (1995) found that among women who do receive recommendation for a screening mammogram, lowincome women are among those least likely to undergo the procedure. The answers to the proposed research questions will be helpful to develop recommendations to assess screening and risk factor control and to design interventions for low-income middle-aged women.…”
Section: Objectivesmentioning
confidence: 99%